A therapeutic benefit of daptomycin against glycopeptide-resistant gram-positive cocci bloodstream infections under neutropenia. Issue 11 (November 2017) - Matsuda, Kensuke; Koya, Junji; Toyama, Kazuhiro; Ikeda, Mahoko; Arai, Shunya; Nakamura, Fumihiko; Okugawa, Shu; Moriya, Kyoji; Kurokawa, Mineo
Abstract: Antibiotic-resistant infections remain to be a major issue for all over the world. Although appropriate diagnosis and rapid treatment initiation are crucially important particularly in immunocompromised patients, selection of antibiotics without identification of causative bacteria is often challenging. A 44-year-old woman with acute myeloid leukemia (AML) under myelosuppression suffered from teicoplanin-resistant gram-positive cocci bacteremia. Taking severe neutropenia due to chemotherapy and glycopeptide-resistance into account, teicoplanin was empirically substituted with daptomycin, which led to prompt defervescence. This microorganism later turned out to be Leuconostoc lactis (L. Lactis), and daptmycin was continued to use based on antimicrobial susceptibility tests. As a result, empiric use of daptomycin successfully controlled glycopeptide-resistant gram-positive cocci bacteremia under neutropenia. This is the first report of daptomycin treatment for L. lactis bacteremia in a patient with AML under neutropenia. Our findings suggest that daptomycin would be a suitable treatment option for glycopeptide-resistant gram-positive cocci bloodstream infections, especially in myelosuppressive patients.